2010
DOI: 10.1021/bm100975w
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Multilayers with pH-Triggered Release of Antibacterial Agents

Abstract: We report on the layer-by-layer design principles of poly(methacrylic acid) (PMAA) ultrathin hydrogel coatings that release antimicrobial agents (AmAs) in response to pH variations. The studied AmAs include gentamicin and an antibacterial cationic peptide L5. Adipic acid dihydrazide (AADH) is a cross-linker which, relative to ethylenediamine (EDA), increases the hydrogel hydrophobicity and introduces centers for hydrogen bonding to AmAs. AmA retention in AADH-cross-linked hydrogels in high-salt solutions was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
143
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(150 citation statements)
references
References 65 publications
4
143
3
Order By: Relevance
“…This suggests that release is determined by the charge balance of gentamicin ionic pairing with PAA units within the film and occurs as ionic pairing is disrupted because of the protonation of PAA in low-pH solutions. In contrast to our previously reported single-component films of all-polymer chemically crosslinked poly(methacrylic acid) LbL hydrogels, 26 clay/PAA layers exhibit significantly enhanced retention of antibiotics within the host matrix in salt solutions, most likely because of favorable dipole-dipole interactions of antibiotics with MMT nanoplatelets. Increasingly, large percentages of gentamicin were released from MMT/PAA films in solutions with lower pH, as confirmed by FTIR and AFM (Figures 4a and b).…”
Section: Responsive Nanocomposite Assembliescontrasting
confidence: 97%
See 3 more Smart Citations
“…This suggests that release is determined by the charge balance of gentamicin ionic pairing with PAA units within the film and occurs as ionic pairing is disrupted because of the protonation of PAA in low-pH solutions. In contrast to our previously reported single-component films of all-polymer chemically crosslinked poly(methacrylic acid) LbL hydrogels, 26 clay/PAA layers exhibit significantly enhanced retention of antibiotics within the host matrix in salt solutions, most likely because of favorable dipole-dipole interactions of antibiotics with MMT nanoplatelets. Increasingly, large percentages of gentamicin were released from MMT/PAA films in solutions with lower pH, as confirmed by FTIR and AFM (Figures 4a and b).…”
Section: Responsive Nanocomposite Assembliescontrasting
confidence: 97%
“…23,24 Moreover, antibacterial surfaces have been designed that can respond to light or pH. 25,26 The present study goes beyond this prior work by describing a new type of coating that was engineered to combine permanent, contactkilling protection with bacteria-triggered, on-demand release of antimicrobials. By exploring clay-containing nanocomposites rather than all-polymer films as matrices to host an antibiotic, we were able to prevent low-level tail release of antibiotics that consequently minimizes the development of antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was known that gentamicin is a commonly used antibiotic agent due to its broad antibacterial spectrum of action [24]. Junge et al [25] have demonstrated that gentamicin modification of a polyvinylidenfluoride mesh induces increased expression of type I collagen mRNA and decreased expression of collagenases (MMP-8 and MMP-13), and consequently, an increased type I collagen ratio at the mesh/host tissue interface.…”
Section: Introductionmentioning
confidence: 99%